The effects of dimmer controlled atmospheric pressure plasma jet to the biophysical structures of HeLa cells - Chin, Fhong Soon; Nafarizal Nayan; Naznin Sultana; Marlia Morsin; Gim, Pao Lim; Nyuk, Ling Ma; Elfa Rizan Rizon; Kian, Sek Tee (Penerbit Universiti Kebangsaan Malaysia, 2020)
Non-thermal atmospheric pressure plasma jet (NTAPPJ) was shown as a promising tool for sterilization, treatment of chronic wounds & tumors. A portable and facile NTAPPJ system will broaden the application of plasma for many other biomedical applications. This paper demonstrates the feasibility of a customized dimmer controllable atmospheric pressure plasma jet (APPJ) in treating HeLa cells. A plasma torch was energized at 8 kVpp and 35 kHz from a neon transformer and discharged with argon gas-producing plasma plume of various gas species. The output intensity of the plasma discharge was adjusted by the voltage input from the dimmer controller circuit. Between 60 – 220 V, a different power output of the dimmer can be varied between 8.4 to 83.6 W, to generate different intensities of non-thermal APPJ (NTAPPJ). The NTAPPJ was then applied to HeLa cells for 20 sec & it was found that cells reduced their adhesion at a dimmer power < 20 W but stayed viable. This progressed to observations of damaged cell body when the power was increased beyond 20 W & the cell membranes shattered when the power was up to 83.6 W. This was due to the ultraviolet rays and reactive oxygen species (ROS), that induced detrimental effects to the cells. The controllable NTAPPJ system, based on dimmer control, induced different levels of effects on the biophysical structures of cells, ranging from reduced cell spread to apoptosis and eventually cell membrane disintegration.